2019
DOI: 10.3329/sja.v17i1.42760
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in anaerobic germination potential and grain yield of rice (oryza sativa) through seed priming

Abstract: A field experiment was conducted during the dry season of 2014 and 2015 at National Rice Research Institute (NRRI), Orissa, India, (20.5ºN, 86°E, and 23.5 meters above mean sea level). Seed priming was employed to enhance the anaerobic germination potential in two near isogenic rice lines (IR64 and IR64-Sub1). Under natural field condition, oxygen concentration in floodwater never dropped to zero. It varied from 3.0 to 5.2 mg L-1. Seed priming with calcium peroxide and seed soaking with water followed by sun d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thus, it is an economical and environmentally friendly choice ( Kumar and Ladha, 2011 ; Zhang et al., 2015 ). Despite the risk of low germination in DSR caused by soil flooding ( Senapati et al., 2019 ), its cost-effectiveness and convenience have made it a widespread practice globally ( Yang et al., 2019 ). However, modern rice varieties do not germinate well when submerged in water, due to the lack of coleoptile elongation and the negative impact of long periods of oxygen deprivation on root and shoot development ( Magneschi and Perata, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is an economical and environmentally friendly choice ( Kumar and Ladha, 2011 ; Zhang et al., 2015 ). Despite the risk of low germination in DSR caused by soil flooding ( Senapati et al., 2019 ), its cost-effectiveness and convenience have made it a widespread practice globally ( Yang et al., 2019 ). However, modern rice varieties do not germinate well when submerged in water, due to the lack of coleoptile elongation and the negative impact of long periods of oxygen deprivation on root and shoot development ( Magneschi and Perata, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…His result revealed that seed priming improved the seedling establishment under anaerobic conditions. Recently, it was observed that rice seed priming followed by sun drying can improve anaerobic germination (Senapati et al, 2019). Angaji et al (2010) identified a few tolerant genotypes of over 8000 genotypes screened for the tolerance of flooding during germination.…”
Section: Introductionmentioning
confidence: 99%